Structures Congress 2015 2015
DOI: 10.1061/9780784479117.188
|View full text |Cite
|
Sign up to set email alerts
|

Loss Estimation of Reinforced Concrete Buildings Considering Aftershock Hazards

Abstract: Current seismic performance methodologies such as FEMA P-58 already have the ability to estimate the direct loss and indirect loss of buildings due to earthquakes using performance based earthquake engineering (PBEE). However, earthquake aftershocks, which have the potential to cause additional damage to buildings, are still not considered in these methodologies. On the other hand, previous seismic performance assessment considering aftershocks cannot account for various post-quake decisions (e.g. evacuation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Zhao et al [19] studied the influence of aftershocks on the seismic fragility of nuclear power plants, the results showed that aftershocks cause additional damage to the structure, leading to a significant increase in the PE values of different damage limit states. Han et al [20] conducted seismic loss estimation of structures using RC frame buildings as a case study and the recorded mainshock-aftershock sequences as the ground motion input. It was concluded that aftershocks increase economic losses and casualties and, to some extent, structural repair costs.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [19] studied the influence of aftershocks on the seismic fragility of nuclear power plants, the results showed that aftershocks cause additional damage to the structure, leading to a significant increase in the PE values of different damage limit states. Han et al [20] conducted seismic loss estimation of structures using RC frame buildings as a case study and the recorded mainshock-aftershock sequences as the ground motion input. It was concluded that aftershocks increase economic losses and casualties and, to some extent, structural repair costs.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, seismic fragility has become a critical and integrated part of the performance-based earthquake engineering (PBEE) framework. To integrate aftershocks into risk analysis, DesRoches developed a framework for aftershock fragility assessment of damaged structures that can account for the damage accumulation [16]. In this paper, the fragility analysis of bridges equipped with UDCMEJ under excitation of seismic sequence is conducted on a continuous girder bridge.…”
Section: Introductionmentioning
confidence: 99%
“…They also have higher expected repair cost for the damage induced by potential earthquakes than their counterparts built per modern codes (Liel and Deierlein 2008). Besides, it has been found that earthquakes aftershocks may cause more damage, higher seismic risks, and addition loss to these buildings (Han, et al 2014a,b;Han, et al 2015). Therefore, approaches to mitigate their seismic risk must be determined and applied.…”
Section: Introductionmentioning
confidence: 99%